2021
DOI: 10.1038/s41467-021-23332-4
|View full text |Cite
|
Sign up to set email alerts
|

DNA origami single crystals with Wulff shapes

Abstract: DNA origami technology has proven to be an excellent tool for precisely manipulating molecules and colloidal elements in a three-dimensional manner. However, fabrication of single crystals with well-defined facets from highly programmable, complex DNA origami units is a great challenge. Here, we report the successful fabrication of DNA origami single crystals with Wulff shapes and high yield. By regulating the symmetries and binding modes of the DNA origami building blocks, the crystalline shapes can be design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…The Porod invariant was observed to saturate after ~24 h suggesting that the reaction had already finished at this time. This is an interesting finding since this time is much shorter than most reaction times reported previously 7 , 13 , 14 , 16 where reactions (employing varying reactant ratios) took up to a week. A possible explanation could be that in these reports the silicification reaction mixture was left to react undisturbed at temperatures slightly below RT, while here during the measurement gentle tumbling was applied at RT in order to avoid sedimentation.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…The Porod invariant was observed to saturate after ~24 h suggesting that the reaction had already finished at this time. This is an interesting finding since this time is much shorter than most reaction times reported previously 7 , 13 , 14 , 16 where reactions (employing varying reactant ratios) took up to a week. A possible explanation could be that in these reports the silicification reaction mixture was left to react undisturbed at temperatures slightly below RT, while here during the measurement gentle tumbling was applied at RT in order to avoid sedimentation.…”
Section: Resultsmentioning
confidence: 54%
“…We demonstrated silicification of single DNA origami nanostructures and 3D DNA origami crystals 15 , resulting in mechanical enforcement. This stabilization allowed us to analyze these fragile origami structures in the dry state, without suffering from structural collapse 13 , 16 . Silicified DNA origami structures are promising candidates for biomedical applications and they play a prominent role for the customized synthesis of inorganic dielectric 2D 17 , 18 and 3D nanomaterials 7 , 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Yourston et al demonstrated the application of programmable RNA nanorings for regulating the formation and properties of silver nanoclusters (AgNCs), which was achieved by chelating AgNCs on cytosine-rich DNA fragments embedded in RNA rings (Yourston et al, 2020). The applications of other nucleic acid nanostructures for guiding the production and assembly of inorganic nanomaterials have also been extensively reported in recent years (Liu et al, 2018;Jing et al, 2019;Shang et al, 2020;Wang et al, 2021a). For more information specifically about this topic, please refer to Heuer-Jungemann and Linko (Heuer-Jungemann and Linko, 2021).…”
Section: Application Of Rna Framework In the Construction Of Nanostructuresmentioning
confidence: 99%
“…DNA origami technology, benefiting from its structural programmability, provides a powerful toolbox to position or encapsulate guest molecules or NPs with nanoscale precision or within 3D scaffold. , On the other hand, crystallization of DNA structures with well-defined shapes allows one to rationalize the assembly of specific lattice types. It has been demonstrated that lattices with designed organizations of DNA motifs in templated lattices can exhibit novel photonic properties . Although a massive progress has been achieved in this regard, the tailorable accommodation of guest species inside DNA frames is rarely investigated.…”
Section: Introductionmentioning
confidence: 99%